A CASE OF THYROTOXIC PERIODIC PARALYSIS AND MODERATE TO SE- VERE GRAVE’S OPHTHALMOPATHY REQUIRING INTRAVENOUS STEROID THERAPY WITH A COMORBIDITY OF CHRONIC HEPATITIS B INFECTION - Heri Krisnata Ginting; Soebagijo Adi (Current Internal Medicine Research and Practice Surabaya Journal, 2022)
Grave’s disease is an autoimmune thyroid disease with several characteristic symptoms and signs. Grave’s ophthalmopathy, an inflammatory disease in the orbital area, is the primary extrathyroid manifestation of Grave’s disease. About 5% of Grave’s ophthalmopathy patients have moderate to severe severity requiring high doses of systemic corticosteroid therapy. Grave’s disease also has a few complications, one of which is thyrotoxic periodic paralysis characterized by hypokalemia and muscle paralysis. Chronic hepatitis B virus infection has the potential to be co-incidence with other diseases (e.g., Grave’s ophthalmopathy). The need for a high dose of corticosteroid therapy in treating Grave’s ophthalmopathy is a risk of reactivation in hepatitis B-infected patients. This paper presented a Grave’s disease patient complicated with Grave’s ophthalmopathy who developed limb muscle weakness. The patient will receive high doses of corticosteroids and prophylactic lamivudine therapy to prevent hepatitis B virus reactivation.